New perspectives on extracorporeal life support: expert teams and precise selection of candidates are transforming pediatric cancer and hematopoietic cell transplantation care - Hurley, Caitlin; Di Nardo, Matteo; Rees, Matthew; Hijano, Diego R.; Said, Ahmed; Sharma, Akshay; Elbahlawan, Lama; Hines, Melissa R.; McArthur, Jennifer A.; Sandhu, Hitesh; Ghafoor, Saad (Frontiers in Oncology, 2025)
Extra Corporeal Life Support (ECLS) for pediatric oncology and stem cell transplant patients over the past two decades has made progress. Substantial improvements in ECLS, Continuous Renal Replacement Therapy (CRRT), and mechanical ventilation techniques, along with enhanced anticoagulation management and infection control, have contributed to better patient outcomes. Additionally, advancements in HLA matching, donor selection, and the management of chemotherapy and transplant complications have further improved survival rates. The authors propose establishing an expert team and a standardized process to evaluate ECLS candidacy, addressing past controversies and optimizing outcomes for this vulnerable population. The criteria for candidacy have evolved significantly, necessitating expert evaluation.